Analysis of Cultural Values in the Drama tōutōu cáng bù zhù (Hidden Love) - Yahya, Zahwa Wetikhanza Avrilia; Siregar, Sheyra Silvia; Supriatnaningsih, Rina; Pamuji, Dian Yuni (Universitas Negeri Semarang, 2024)
Drama can be said to be a realistic depiction of a character's life. Culture itself is the customs, traditions and beliefs that exist in society so that culture is always present in drama. Life values ​​also do not escape drama elements, one of which is in the drama 偷偷藏不住 (tōutōu cáng bù zhù). This research aims to describe the cultural values ​​contained in the drama 偷偷藏不住 (tōutōu cáng bù zhù) based on Edwar Djamaris' theory, and describe the cultural symbols contained in the drama 偷偷藏不住 (tōutōu cáng bù zhù) using theory Charles Sanders Pierce's semiotics in two sides, namely signs and objects. This type of research is qualitative descriptive research using note-taking techniques. Data collection uses note-taking techniques and the results of previous research, journals, books and other documents regarding cultural values. Data analysis techniques use data reduction, data display and drawing conclusions. The result is that there are five cultural values ​​contained in the drama 偷偷藏不住 (tōutōu cáng bù zhù) based on the theory of cultural values ​​by Edwar Djamaris, namely the cultural value of human relationship with God, the cultural value of human relationship with society, the cultural value of human relationship with self. itself, the cultural value of human relations with humans, and the cultural value of human relations with nature. Researchers also found six cultural symbols contained in the drama 偷偷藏不住 (tōutōu cáng bù zhù) based on semiotic theory by Charles Sanders Pierce, namely red ornaments, lanterns, paper sticks, red packets, Chinese knots, and the writing 囍.